Pokeener: Sistem Aiot Untuk Otomatisasi Konversi Sampah Organik Menjadi Bioetanol Dalam Mendukung Ekonomi Sirkular Berkelanjutan. - Hendry Dwi Jatmiko; Lintang Buwono; Aditya Nikko Arya Putra (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Organic waste originating from food leftovers, leaves, wood, and other natural materials accounts for approximately 60–70% of the total 67.8 million tons of waste generated in Indonesia in 2020. This large proportion indicates significant potential for organic waste to be converted into bioethanol, an environmentally friendly renewable fuel that also reduces environmental pollution. Bioethanol offers a green energy solution to decrease dependence on fossil fuels. In this context, Artificial Intelligence of Things (AIoT) technology plays an important role in optimizing the bioethanol production process. The system integrates artificial intelligence and Internet of Things (IoT) devices to automatically monitor and control fermentation conditions. Key sensors used include the DS18B20 for temperature monitoring, HI1131B for pH measurement, MQ-3 for ethanol gas detection, and DHT11 for humidity monitoring. Sensor data are processed using supervised learning algorithms to automatically adjust process parameters. This study involves laboratory experiments, SolidWorks-based simulations, and literature review, resulting in an efficient bioethanol production system that supports a sustainable circular economy.